2018
DOI: 10.3389/fnhum.2018.00432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neuromuscular Electrical Stimulation Training on the Finger Extensor Muscles for the Contralateral Corticospinal Tract in Normal Subjects: A Diffusion Tensor Tractography Study

Abstract: Objectives: Neuromuscular electrical stimulation (NMES) is a popular rehabilitative modality to improve motor function of the extremities and trunk. In this study, we investigated changes of hand function and the contralateral corticospinal tract (CST) with treatment by NMES on the finger extensor muscles for 2 weeks, using serial diffusion tensor tractography (DTT).Methods: Thirteen right handed normal subjects were recruited. Treatment was applied to the left hand (the NMES side), and the right hand was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…There were 40 articles (48.2%) that reported the effects of chronic peripheral stimulation (training), with 31, six and three applying ES, VB or ND, respectively; and 43 (51.8%) that investigated the acute effects, with 22, 12 and nine applying ES, VB or ND, respectively. Among the 40 studies that used chronic stimulation, the typical protocols involved 2–5 sessions per week (except for one ES study [ 80 ] that applied 10 sessions per week, and three ES studies [ 51 , 92 , 98 ] and one VB study [ 111 ] that trained for seven sessions per week), for 1–12 weeks with a total of 9–36 training sessions (with exception of one ES study [ 55 ] that lasted 56 weeks and involved 280 sessions) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were 40 articles (48.2%) that reported the effects of chronic peripheral stimulation (training), with 31, six and three applying ES, VB or ND, respectively; and 43 (51.8%) that investigated the acute effects, with 22, 12 and nine applying ES, VB or ND, respectively. Among the 40 studies that used chronic stimulation, the typical protocols involved 2–5 sessions per week (except for one ES study [ 80 ] that applied 10 sessions per week, and three ES studies [ 51 , 92 , 98 ] and one VB study [ 111 ] that trained for seven sessions per week), for 1–12 weeks with a total of 9–36 training sessions (with exception of one ES study [ 55 ] that lasted 56 weeks and involved 280 sessions) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, Jang et al 10 reported that “walnut-rolling” with the non-dominant hand improved the ability to manipulate a peg, raised grip and pinch strengths, and significantly increased the apparent number of fibers in contralateral CFT of the non-dominant hand of healthy participants. Jang and Seo 11 reported that pinch strength and peg manipulation measures increased, and the contralateral apparent CFT volume rose significantly after two weeks of peripheral stimulation of the extensor digitorum muscle of healthy volunteers. Jang and Jang 12 had shown that the apparent number of fibers of the CFT of the uninjured hemisphere increased when dominant hand lateralization changed after stroke.…”
Section: Introductionmentioning
confidence: 99%